Factors associated with advanced-stage oral and oropharyngeal squamous cell carcinoma in a Brazilian population - Rebeca Cardoso Pedra; Clarice Lima Álvares da Silva; Ismênia Edwirges Bernardes; Francielle Silvestre Verner; Karla Machado Andrade; Rafael de Sousa Santos; Sibele Nascimento de Aquino (Universidade Estadual de Campinas, 2021)
Diagnosis of oral and oropharyngeal cancer in advanced stages may be associated with social nature factors, access to health care, education, occupation, and behavioral/ cultural factors. Aim: To determine the factors related to high clinical-staging in patients diagnosed with squamous cell carcinoma in the oral and oropharyngeal region in a Cancer Center in Brazil between 2009 and 2015. Methods: It is an epidemiological, retrospective, and exploratory study. Patients diagnosed with squamous cell carcinoma had their medical records analyzed. The variables considered were sociodemographic, lifestyle, and disease characteristics. Descriptive and exploratory tests (Pearson's, chi-square test and, Student's t-test) were realized. Results: We analyzed 365 patient records, among which 289 (79.17%) were male, and 73 (20.0%) were female. Age ranged from 16 to 101 years, with a mean of 61.13. Regarding education, 157 (43.01%) studied < 8 years, 103 (28.21%) were illiterate and 102 (27.94%) studied > 8 years. 305 (83.56%) patients live in urban areas. There was an association between high clinical-staging and low educational level. For high clinical-staging, symptomatology, tobacco, and alcohol intake as well. Conclusion: Patients with low educational levels tend to report the disease later, and their diagnostics occurred in advanced stages. Thus, specific public health policies for this population, including access to dental care to recognize the clinical signs and early diagnosis, are necessary.